UPAYA PEMBERDAYAAN MASYARAKAT LOKAL PADA DAYA TARIK WISATA LEMO, KECAMATAN MAKALE UTARA, KABUPATEN TANA TORAJA - Seriany Tonglo; I Made Adikampana (JURNAL DESTINASI PARIWISATA, 2016)
Abstract The purposed of this paper is to find out the empowerment efforts by government to developing the local communities at tourist attraction of Lemo, especially in the field of tourism. Thus, it’s expected the local communities can play an active role in developing of tourism industry in their place. The author directly go to the field for observation and data collection in order to know the existing problems. The collection of data used in this study were obtained through observation techniques, documentation, library research, and interviews on informers.  Informers are deemed to know about the problems in community empowerment, by using a qualitative descriptive analysis. The author found out that  there are many constraints faced by the local communities such the lack of knowledge of the local communities in the field of tourism and the lack of the number of people who can speak  foreign languages, so it’s need participation from government and other related sector in overcoming the obstacles encountered by the community.